Liszt and Mahler in the postmodern filmic visions of Ken Russell - Golianek, Ryszard Daniel (Interdisciplinary Studies in Musicology, 2018)
The British film and television director Ken Russell is esteemed principally for creating filmic biographies of composers of classical music. In the 70s, he shot his most original films on musical subjects: fictionalised, highly individual composer biographies of Mahler (Mahler) and Liszt (Lisztomania), which are the subject of the article. Neither of the films is in the least a realistic documentary biography, since Russell’s principal intention was to place historical biographical facts in cultural contexts that were different from the times in which Mahler and Liszt lived and worked. This gave rise to a characteristically postmodern collision of different narrative and expressive categories. Russell’s pictures remain quite specific commercial works, exceptional tragifarces, in which the depiction of serious problems is at once accompanied by their subjection to grotesque deformation and the demonstration of their absurdities or denaturalisation. The approach proposed by this British director, in which serious issues are accompanied by elements of triteness, is a hallmark of his style. The director’s musical interests are reflected by the fundamental role of music in the structure of his cinematographic works. The choice of musical works also denotes a kind of aesthetic choice on the director’s part, especially when the composers’ biography comes into play.